2008
DOI: 10.1111/j.1365-2249.2008.03594.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen exhibits type II collagen protective effects and attenuates collagen-induced arthritis in rats

Abstract: SummaryAs anti-inflammatory treatments used in rheumatoid arthritis, such as glucocorticoids, often result in secondary detrimental effects on bone health, the objective of this study was to investigate the effects of oestrogen therapy (ET) on the development and activity of collagen-induced arthritis (CIA) in rats, with a focus on assessment of chondroprotective effects using biomarkers of type II collagen degradation. Forty female Lewis rats were allocated into four intervention groups: (i) control + vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 36 publications
(45 reference statements)
2
39
3
2
Order By: Relevance
“…10,49 However, estrogen has been shown to protect against CIA in DBA/ 1LacJ mice and Lewis rats. 94,95 What could account for this discrepancy? One possibility is that the acute inflammation including macrophages and neutrophils that is induced by CFA/collagen in the CIA model is inhibited by estrogen, as discussed in the previous section.…”
Section: Rheumatoid Arthritis: Acute Mixed Cell and Antibody-mediatedmentioning
confidence: 99%
“…10,49 However, estrogen has been shown to protect against CIA in DBA/ 1LacJ mice and Lewis rats. 94,95 What could account for this discrepancy? One possibility is that the acute inflammation including macrophages and neutrophils that is induced by CFA/collagen in the CIA model is inhibited by estrogen, as discussed in the previous section.…”
Section: Rheumatoid Arthritis: Acute Mixed Cell and Antibody-mediatedmentioning
confidence: 99%
“…There is also some evidence that oral contraceptives have a protective role in RA 33 . In animal models, estrogen treatment delayed disease onset and reduced the degree of cartilage degradation in rats with collagen-induced arthritis 34 .…”
Section: Estrogens and Rheumatoid Arthritismentioning
confidence: 99%
“…Reproduced with permission from Elsevier Masson [96] incidence of joint pain peaks at 50-59 years in the general population. Some preclinical studies have shown a protective effect of oestrogen in arthritis and on pro-inflammatory genes [24,25]. Clearly, there are several possible causes of arthralgia in a non-breast cancer population, which can make it difficult to elucidate one particular cause.…”
Section: Role Of Oestrogenmentioning
confidence: 99%